MORPHOMETRY AND IDENTIFICATION OF HISTOLOGICAL CHARACTERISTICS OF BALI CATTLE OVARIES - Ni Putu Amasya Chikita Rivanny; Tjok Gde Oka Pemayun; Ni Luh Eka Setiasih (Buletin Veteriner Udayana, 2025)
Bali cattle (Bos sondaicus) are said to be fertile because the right and left ovaries of Bali cattle have the same opportunity in their reproductive activity. Ovaries activity can be reviewed morphometrically and histologically to determine the characteristics of each estrus phase. This study was conducted with the aim of determining the differences in morphometry of the right and left ovaries in Bali cattle, as well as identifying the histological features of the ovaries of Bali cattle. The morphometry study of the right and left ovaries was conducted descriptively quantitatively where the data was processed statistically with a paired sample T- test. Identification of histological characteristics was conducted descriptively qualitatively. The results of the morphometry calculations stated that the weight and width of the right and left ovaries of Bali cattle were not significantly different (P>0.05), while the length of the ovaries was significantly different (P<0.05). The results of histological identification can be identified through the development of follicles and corpus luteum to become corpus albicans.